ASSOCIATION OF MATERNAL CHARACTERISTICS WITH COMPLICATIONS OF PREGNANCY: A CROSS-SECTIONAL STUDY AMONG MIDDLE SOCIOECONOMIC PREGNANT WOMEN - NEKKANTI, VINEELA; KISHORE, GITHA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of the study was to determine the association of maternal characteristics with complications of pregnancy among middle socioeconomic women. Methods: The enrolled subjects were divided into two groups as complicated and uncomplicated group based on the occurrence of complications in current pregnancy and their sociodemographic details along with present and past medical and medication history was collected. Results: The mean age of the study subjects was 25.33±4.22 years. Maternal characteristics such as age, parity, body mass index, maternal education, and employment status did not have a statistically significant association with the complications of pregnancy at p<0.05. However, the first antenatal visit at the gestational age <8 weeks had a statistically significant association with the complications of pregnancy at p=0.02. Conclusion: Early initiation of antenatal care along with adequate antenatal visits may reduce the risk of complications of pregnancy.